MANAJEMEN LABA, PROFITABILITAS, UKURAN BANK, DEWAN KOMISARIS DAN CORPORATE SOCIAL RESPONSIBILITY BANK SYARIAH - Putri, Elsya Septiani (JURNAL FAIRNESS, 2019)
This study aims to examine the effect of Earnings Management, Profitability, Bank Size, and Board of Commissioners Size on Corporate Social Responsibility (CSR). The sample of this study consisted of 8 Sharia Commercial Banks registered in the Indonesian Sharia Banking Statistics. Testing the hypothesis in this study using multiple linear regression analysis by following the autoregressive process of order 1 or AR (1) which is estimated simultaneously using the Eviews application. The results of this study indicate that earnings management has a positive effect on Corporate Social Responsibility (CSR), while profitability, bank size, and board size do not affect Corporate Social Responsibility (CSR).